UNIT 17.20 Porphyria Diagnostics—Part 1: A Brief Overview of the Porphyrias. (1st July 2015) - Ramanujam, Vaithamanithi‐Mudumbai Sadagopa; Anderson, Karl Elmo
Abstract : Porphyria diseases are a group of metabolic disorders caused by abnormal functioning of heme biosynthesis enzymes and characterized by excessive accumulation and excretion of porphyrins and their precursors. Precisely which of these chemicals builds up depends on the type of porphyria. Porphyria is not a single disease but a group of nine disorders: acute intermittent porphyria (AIP), hereditary coproporphyria (HCP), variegate porphyria (VP), δ‐aminolevulinic acid dehydratase deficiency porphyria (ADP), porphyria cutanea tarda (PCT), hepatoerythropoietic porphyria (HEP), congenital erythropoietic porphyria (CEP), erythropoietic protoporphyria (EPP), and X‐linked protoporphyria (XLP). Each porphyria results from overproduction of heme precursors secondary to partial deficiency or, in XLP, increased activity of one of the enzymes of heme biosynthesis. Taken together, all forms of porphyria afflict fewer than 200, 000 people in the United States. Based on European studies, the most common porphyria, PCT, has a prevalence of 1 in 10, 000, the most common acute porphyria, AlP, has a prevalence of ∼1 in 20, 000, and the most common erythropoietic porphyria, EPP, is estimated at 1 in 50, 000 to 75, 000. CEP is extremely rare, with prevalence estimates of 1 in 1, 000, 000 or less. Only six cases of ADP are documented. The current porphyria literature is very exhaustive and a brief overview of porphyria diseases is essential in order for the reader to better appreciate the relevance of this area of research prior to undertaking biochemical diagnostics procedures. This unit summarizes the current knowledge on the classification, clinical features, etiology, pathogenesis, and genetics of porphyria diseases. © 2015 by John Wiley & Sons, Inc.